(untitled) (Medico Legal Update, 2020)
Poisoning is an important health problem in every country of the world. Occupational exposure to industrial chemicals and pesticides, accidental or intentional exposure to household and pharmaceutical products and poisoning due to venomous animals, Toxic plants and food contamination, all contribute to morbidity and mortality. Poison is a substance that being soluble in the blood either destroys life or impairs seriously the functions of one or more organs of the body. Poison can be defined as, a substance (solid, liquid or gas) which if introduced in a living body or brought in contact with any part thereof will produced ill health or death by its constitutional or local effects or both.1 Due to rapid development in the field of science and technology and vast growth in the industrial and agricultural sector, the poisoning is spreading like a wild fire. Poisoning is a medical emergency and the patients are invariably admitted to the hospital through emergency services. The poisoning may be suicidal, accidental or homicidal. With this background, the present study has been carried out to determine the profile of poisoning cases, autopsied at SSIMS & RC, Davangere, Karnataka. The study revealed that victims of rural population (68.9%) are highest among the habitation, followed by urban population. Most of the victims are married people (63.9%). Most of the victims were educated with matriculation (62.3%). Most of the poisoning cases are seen in Hindu religion (91.8%). Most of the cases were seen in winter season (42.6%) and in most of the cases the victims has consumed the poison at home (83.9%).